Training of students-philologists comic genres of professional speech - Surkova A. P. (Interactive science, 2016)
in clause the model of training of the students – philologists to creation and use of speech comic genres (in particular, such, as the comic story, anecdote, historical anecdote, joke, comic aphorism and winged words)) in the pedagogical purposes is considered (examined). It will promote, on our sight, optimization of professional dialogue of the teacher in an educational situation.
Keywords: педагогическое общение; жанры комического; профессиональная речь студентов-филологов; comic genres; professional speech of philology students; teacher communication